Two new species of Dasybasis Macquart from the Peruvian Andes of Cusco (Diptera: Tabanidae: Diachlorini) - González, Christian R.; Yábar, Erick (Zootaxa, 2024)
Two new horse fly species, Dasybasis mancoi sp. nov. and D. huaynai sp. nov. (Diptera: Tabanidae: Diachlorini), are described from the Peruvian Andes near Cusco on the basis of morphological features, including those of the female genitalia. Digital photographs of both species and of the terminalia of both females and of one male are provided. The two new species are related to D. bulbula Coscarón & Philip, as evidenced by their similar morphological characteristics.